ERACS Method as a Solution to Allow Hospital and Patient Financing - Tansya Sushan Purnaningrum (The Eastasouth Management and Business, 2023)
ERACS (Enhanced Recovery After Caesarian Surgery) is a fast post-SC recovery program, namely a series of treatments starting from preoperative preparation, during surgery, and postoperative care to patient discharge. The ERACS concept is the development of the Enhanced Recovery After Surgery (ERAS) concept, where the ERAS concept was originally used in digestive surgery. The purpose of this study was to find out whether the eracs method could be used as a solution to ease the burden on hospital and patient costs. This research method was carried out using a literature review approach with a library approach. The nature of the research used in this research is a prescriptive design. The results of this study were then analyzed qualitatively. Based on the results of the study it can be concluded that the Enhanced Recovery After Caesarean Surgery (ERACS) method is the newest method performed for cesarean delivery. This method emphasizes reducing the anesthetic dose so that the patient does not need to spend a long time in the hospital. Because, if the patient stays in the hospital for too long, this will have an impact on increasing the cost of hospitalization. This method can reduce the financial burden on both patients and healthcare facilities. This will help a mother to care for her baby much earlier without compromising her safety and satisfaction. Hospitals will have an advantage in terms of decreased beds and thus the number of patients treated will increase and healthcare resources will be increased efficiently used.